2017
DOI: 10.1186/s13054-017-1737-7
|View full text |Cite
|
Sign up to set email alerts
|

Transthoracic echocardiography: an accurate and precise method for estimating cardiac output in the critically ill patient

Abstract: BackgroundCardiac output (CO) monitoring is a valuable tool for the diagnosis and management of critically ill patients. In the critical care setting, few studies have evaluated the level of agreement between CO estimated by transthoracic echocardiography (CO-TTE) and that measured by the reference method, pulmonary artery catheter (CO-PAC). The objective of the present study was to evaluate the precision and accuracy of CO-TTE relative to CO-PAC and the ability of transthoracic echocardiography to track varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(106 citation statements)
references
References 29 publications
4
97
1
4
Order By: Relevance
“…A recent study showed moderate consistency in hemodynamic assessment of mechanically ventilated patients with septic shock using PiCCO and CCM echocardiography [12]. The correlation between CO calculated by manual VTI and CO measured by PiCCO is about 0.95 as reported previously [13]. The corresponding correlation in the present study is 0.911, which seems to be slightly lower than that of manual determination.…”
Section: Discussionsupporting
confidence: 75%
“…A recent study showed moderate consistency in hemodynamic assessment of mechanically ventilated patients with septic shock using PiCCO and CCM echocardiography [12]. The correlation between CO calculated by manual VTI and CO measured by PiCCO is about 0.95 as reported previously [13]. The corresponding correlation in the present study is 0.911, which seems to be slightly lower than that of manual determination.…”
Section: Discussionsupporting
confidence: 75%
“…However, few studies have validated the accuracy of echocardiography compared to the ‘gold standard’ pulmonary artery catheter (PAC) . One recent study in 38 mechanically ventilated patients found high correlation (r=0.95) between cardiac output measured by PAC and cardiac output measured by transthoracic echocardiography . The techniques are not interchangeable when measuring cardiac output, but they may be interchangeable to follow directional changes in cardiac output …”
Section: Imagingmentioning
confidence: 99%
“…114 One recent study in 38 mechanically ventilated patients found high correlation (r=0.95) between cardiac output measured by PAC and cardiac output measured by transthoracic echocardiography. 115 The techniques are not interchangeable when measuring cardiac output, but they may be interchangeable to follow directional changes in cardiac output. 114 Echocardiography has been strongly recommended by consensus groups in patients presenting with circulatory failure.…”
Section: Echocardiography For Monitoring Cardiac Outputmentioning
confidence: 99%
“…If one divides the cardiac output by the Body Surface Area (BSA) one gets the Cardiac Index (CI). This method is very accurate and can be considered as gold standard function [36].…”
Section: Cardiac Outputmentioning
confidence: 99%